Urban violence is not (necessarily) a way of life: Towards a political economy of conflict in cities - Dennis Rodgers (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
As the world moves towards its so-called urban 'tipping point',urbanization in the global South has increasingly come to be portrayed as the portent of a dystopian future characterized by ever-mounting levels of anarchy and brutality. The association between cities, violence, and disorder is not new, however. In a classic article on 'Urbanism as a way of life', Louis Wirth (1938: 23) famously links cities to 'personal disorganization, mental breakdown, suicide, delinquency, crime, corruption, and disorder'. He does so on the grounds that the urban context constituted a space that naturally generated particular forms of social organization and collective action as a result of three key attributes: population size, density, and heterogeneity. Large numbers lead to a segmentation of human relations, the pre-eminence of secondary over primary social contact, and a utilitarianization of interpersonal relationships. Density produces increased competition, accelerates specialization, and engenders glaring contrasts that accentuate social friction. Heterogeneity induces more ramified and differentiated forms of social stratification, heightened individual mobility, and increased social fluidity. While large numbers, density, and heterogeneity can plausibly be considered universal features of cities, it is much less obvious that they necessarily lead to urban violence. This is a standpoint that is further reinforced by the fact that not all cities around the world - whether rapidly urbanizing or not - are violent, and taking off from Wirth's characterization of the city, this paper therefore seeks to understand how and why under certain circumstances compact settlements of large numbers of heterogeneous individuals give rise to violence, while in others they don't, focusing in particular on wider structural factors as seen through the specific lens of urban gang violence.
Keywords: K42; R00; Z10; 330; violence; gangs; Chicago School of Sociology; Wirth; Urbanisierung; Sozialer Konflikt; Gewalt; Organisierte Kriminalität; Stadtsoziologie